2011
DOI: 10.1159/000325705
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Gender Inequities in the Evaluation of Referred Short Children

Abstract: Aims: To examine ethnicity and gender differences in the evaluation of referred children with short stature and to investigate adherence of the primary care evaluation to published guidelines. Methods: Cross-sectional study in a referral center. 371 short patients aged 2–18 years were included. Outcome measures were patient’s growth characteristics, final diagnosis, and prevalence of pre-referral patient data. Results: The study population was composed of 239 Bedouin children and 132 Jewish children (p < 0.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…In an observational study of over 21,000 children referred for short stature from 237 institutions and practices, the mean age at referral was 8.6 years, 69% were male, and the mean height SD was −2.1 (7). Others have reported increased referral rates for males ranging from 61% to 65% (8)(9)(10). In our population, females were referred earlier than males despite the finding that a greater proportion of males had a PED (50.8% versus 32.3% females).…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In an observational study of over 21,000 children referred for short stature from 237 institutions and practices, the mean age at referral was 8.6 years, 69% were male, and the mean height SD was −2.1 (7). Others have reported increased referral rates for males ranging from 61% to 65% (8)(9)(10). In our population, females were referred earlier than males despite the finding that a greater proportion of males had a PED (50.8% versus 32.3% females).…”
Section: Discussioncontrasting
confidence: 71%
“…This retrospective chart review showed that there was a high frequency of GCs at initial assessment of patients referred to our centre for short stature: 72% compared to reported rates of 41 to 59% (8,9). This was likely attributable to our standard clinical practice, wherein following receipt of a referral for short stature, repeated requests were made to the referring physician for previous measurements.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In some cases, a lack of trained staff may mean that children are unable to get routine growth checks at school (44). Indeed, as recently as 2011, Yardeni et al showed that adherence to guidelines for evaluation of short stature in the primary clinic referring children to a specialist unit was inadequate; children were frequently referred without important data on previous growth and parental height, and many laboratory tests crucial to the primary care physician's evaluation were lacking (45).…”
Section: Guidelines For Growth Monitoringmentioning
confidence: 99%
“…However, the study indicated that up to 25% of children with pathological growth failure may not be identified and other factors need to be considered, such as clinical examination and phenotype. There is a strong gender bias in referrals for short stature, with girls much less likely to be referred than boys ( 15 , 16 ) and an ethnic bias may also be present ( 16 ). In all cases, up-to-date growth standards should be used, and wherever possible they should be population specific.…”
Section: Clinical Indications For Referral For Short Staturementioning
confidence: 99%